Code Switching Found in Daniel Mananta’s Utterances on YouTube Channel - Petrus Stefanus Pagul; I Gusti Agung Sri Rwa Jayantini; Ni Nyoman Deni Ariyaningsih (RETORIKA: Jurnal Ilmu Bahasa, 2022)
This study concerns with code-switching in Daniel Mananta’s utterance. This study aims to answer the research problems, which are: (1) to classify the types of code switching found in Daniel Mananta’s utterance and (2) and to analyze the function of code switching. Descriptive qualitative method was applied to identify the data. Code-switching was described according to a theory proposed by Poplack (1980) to classify the types of code-switching and the theory by Apple& Muysken (1987) to describe the function of code switching found in Daniel Mananta’s utterance. The result of this study shows that all types of code switching and six function of code-switching were found. First, the three types of code-switching were found, namely tag switching, intra-sentential switching, and inter-sentential switching, in which the most dominant switching is intra-sentential switching. It occurs because Daniel Mananta looks more comfortable when using words, clauses, and phrases in one sentence to convey motivational messages. Second, six functions of code-switching were found, namely referential function, directive function, expressive function, phatic function, metalinguistic function, poetic function. The most dominant function is phatic function because Daniel Mananta’s feels free and more comfortable expressing his emotional feelings in a language that is used in his daily language.